Answer:
(-1,3)
Step-by-step explanation:
–2x – 9y=-25
-4x – 9y=-23
Multiply the second equation by -1
4x + 9y=23
Add this to the first equation
–2x – 9y=-25
4x + 9y= 23
-----------------------
2x = -2
Divide each side by 2
2x/2 = -2/2
x = -1
Now we need to find y
4x+9y = 23
4(-1) +9y = 23
-4 +9y = 23
Add 4 to each sdie
-4+4 +9y = 23+4
9y = 27
Divide each side by 9
9y/9 = 27/9
y =3
Answer: 0.875
Step-by-step explanation: How I got this answer is I used Division, (7 ÷ 8= 0.875)
Hope this helps, Have a great day/night!
~IFoundJiminsLostJams~
Answer: - 48 (edit: omg i didnt see the minus)
Step-by-step explanation: i mean, only z multiply x
z = 12
x = 4
zx
= z multiply x
= 12 x - 4
= - 48
^_____^
The formula for slope is (y-y1)/(x-x1).
1 = x
-1 = y
-2 = x2
8 = y2
You would plug those into the formula: (-1-(-2))/(-1-8) and that would equal to: 1/(-9).
Answer:
1641885
Step-by-step explanation: